2021
DOI: 10.1002/bab.2165
|View full text |Cite
|
Sign up to set email alerts
|

Glucose oxidase: Applications, sources, and recombinant production

Abstract: Glucose oxidase is a subset of oxidoreductase enzymes that catalyzes the transfer of electrons from an oxidant to a reductant. Glucose oxidases use oxygen as an external electron acceptor that releases hydrogen peroxide (H 2 O 2 ). Glucose oxidase has many applications in commercial processes, including improving the color and taste, increasing the persistence of food materials, removing the glucose from the dried egg, and eliminating the oxygen from different juices and beverages. Moreover, glucose oxidase, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 114 publications
(222 reference statements)
0
41
0
Order By: Relevance
“…The GOx-based catalysis also uses oxygen as an electron acceptor. As such an important bioreaction involves glucose, oxygen, H 2 O 2 , and electrons, GOx has been applied to several domains, ranging from food and pharmaceutical sciences to biosensors and bioelectronics (such as glucose biosensors and enzymatic biofuel cells) [ 3 , 4 ]. Nevertheless, a formidable challenge pertaining to long-term stability, particularly in fluctuating temperature environments, impedes the progress of GOx-based biotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…The GOx-based catalysis also uses oxygen as an electron acceptor. As such an important bioreaction involves glucose, oxygen, H 2 O 2 , and electrons, GOx has been applied to several domains, ranging from food and pharmaceutical sciences to biosensors and bioelectronics (such as glucose biosensors and enzymatic biofuel cells) [ 3 , 4 ]. Nevertheless, a formidable challenge pertaining to long-term stability, particularly in fluctuating temperature environments, impedes the progress of GOx-based biotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…Ge et al (2012) have shown that when the oxygen concentration was 1%, the growth and reproduction of microorganisms were significantly inhibited after use of GOD, which can prolong the shelf life of food. GOD can efficiently remove oxygen in foods, protect reducing substances in foods from being destroyed by oxidation and extend the shelf life of foods, which can serve as an ideal preservative (Khatami et al, 2021). Shen et al (2016) found that GOD has the optimal preservative effect at 4 °C.…”
Section: Glucose Oxidasementioning
confidence: 99%
“…that specifically catalyzes the oxidation of β‐ Ɗ ‐glucose to Ɗ‐glucono‐1,5‐lactone or Ɗ‐glucono‐δ‐lactone with molecular oxygen as the electron acceptor, releasing hydrogen peroxide (Farid et al, 2013). GOX is a member of the oxidoreductase family of enzymes, which include oxidases, peroxidases, dehydrogenases, etc., that catalyzes reactions involving electron transfer from the oxidizing agents to the reducing agents in live organisms (Khatami et al, 2021; Trisolini et al, 2019). The presence of GOX enzyme was first reported by Müller (1928) in Aspergillus niger and Penicillium glaucum extracts and was subsequently purified (Leskovac et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is also industrially used for gluconic acid (GA) production. GA is used in food, beverage, pharmaceutical, and textile industries and also in biofuel production (Khatami et al, 2021), and the consumption of GA and its derivatives is approximately 10 5 tons/year (Fernandes et al, 2021; Kornecki et al, 2020; Pal et al, 2019). However, for a cost‐effective and eco‐friendly process of GA production, the production of GOX enzyme by molds such as Aspergillus and Penicillium spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation